Simultaneous optimization on biolubricants obtained through a quaternary mixture of vegetable oils: application of the desirability function - Maria Flávia Rodrigues Starling Araujo; Vânya Márcia Duarte Pasa; Camila Nunes Costa Corgozinho (The Journal of Engineering and Exact Sciences)
To reduce the environmental impacts and the costs of the production of biolubricant, this work proposes the use of vegetable oil mixtures that have not been chemically modified. Formulations of biolubricants were proposed with the use of jatropha curcas, castor, macauba kernel, and macauba pulp oils since these have potential physical-chemical properties to generate a high-performance biolubricant. A simplex centroid quaternary mixture design was used with the desirability function for the simultaneous improvement of the viscosity index and lubricity in the blends. Good results for these properties were obtained for some blends, especially that with macauba pulp oil, which presented comparable or superior performance to those for vegetable oils chemically modified. Macauba has been pointed out as a new feedstock for biodiesel, green diesel, and sustainable aviation fuels (SAF), and its use as eco-lubricant can aggregate the value of this new palm oil, promoting social, economic, and ambient benefits.